2018
DOI: 10.1021/acsmedchemlett.8b00289
|View full text |Cite
|
Sign up to set email alerts
|

Tariquidar-Related Chalcones and Ketones as ABCG2 Modulators

Abstract: ABC transporters, including ABCG2, play a vital role in defending the human body against the vast range of xenobiotics. Even though this is beneficial for human health, these protein transporters have been implicated in the emerging resistance of cancer cells to a variety of structurally and functionally diverse anticancer drugs. In order to investigate their role in resistance, potent and selective ABCG2 modulators have been described in the literature. A leading class of modulators are the tariquidar analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…In addition to the aforementioned chalcone hybrids, other hybrids, such as chalcone–ferrocene [ 95 , 96 , 97 ], chalcone–furan/thiophene hybrids [ 98 , 99 , 100 , 101 ], chalcone–pyridine/pyrimidine hybrids [ 102 , 103 , 104 , 105 , 106 ], chalcone–quinoline/quinolone hybrids [ 107 , 108 , 109 , 110 , 111 ], chalcone–quinoxaline/quinazolinone hybrids [ 112 , 113 , 114 ], chalcone-quinone hybrids [ 115 , 116 , 117 ], chalcone–triazine hybrids [ 118 , 119 ], and chalcone–dithiocarbamate hybrids [ 120 , 121 ] also showed certain anticancer activity.…”
Section: Strategies Employed To Produce Anticancer Chalconesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aforementioned chalcone hybrids, other hybrids, such as chalcone–ferrocene [ 95 , 96 , 97 ], chalcone–furan/thiophene hybrids [ 98 , 99 , 100 , 101 ], chalcone–pyridine/pyrimidine hybrids [ 102 , 103 , 104 , 105 , 106 ], chalcone–quinoline/quinolone hybrids [ 107 , 108 , 109 , 110 , 111 ], chalcone–quinoxaline/quinazolinone hybrids [ 112 , 113 , 114 ], chalcone-quinone hybrids [ 115 , 116 , 117 ], chalcone–triazine hybrids [ 118 , 119 ], and chalcone–dithiocarbamate hybrids [ 120 , 121 ] also showed certain anticancer activity.…”
Section: Strategies Employed To Produce Anticancer Chalconesmentioning
confidence: 99%
“…The best derivative ( 75 ) was selective for ABCG2 over P-glycoprotein and MRP1 and stimulated ABCG2 basal ATPase activity [ 183 ]. Peña-Solórzano et al found that tariquidar-related chalcones ( 76 ) exhibited selectivity for ABCG2 to a greater extent than the transporters ABCB1 and ABCC1 [ 109 ]. Notably, novel quinolone chalcones ( 77 ) synthesized by Lindamulage et al could overcome multidrug resistance by impeding MRP1 function while maintaining strong inhibition of microtubule activity [ 111 ].…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…Structure-activity relationship studies suggested that the presence of a 4-tert-butylphenyl moiety on the inverted amide (compound 92), conferred the best P-gp inhibitory activity (IC 50 = 1. In search for more stable analogues, Peña-Solórzano et al [163] prepared a series of tariquidar analogues with chalcone and ketone moieties, according to a bioisosteric approach [ Figure 16]. These compounds were investigated for their inhibitory activity and selectivity toward BCRP.…”
Section: Tariquidar Derivativesmentioning
confidence: 99%
“…In search for more stable analogues, Peña-Solórzano et al [ 163 ] prepared a series of tariquidar analogues with chalcone and ketone moieties, according to a bioisosteric approach [Figure 16] . These compounds were investigated for their inhibitory activity and selectivity toward BCRP.…”
Section: Tariquidar Derivativesmentioning
confidence: 99%
“…Proteínas transportadoras de efluxo ABC, como ABCB1 e ABCG2, estão relacionadas à resistência de glioblastoma frente à quimioterapia e menor sobrevida do paciente (EMERY et al, 2017;MUNOZ et al, 2014;SCHAICH et al, 2009;WIJAYA;FUKUDA;SCHUETZ, 2017 (FALLACARA et al, 2019;PERAZZOLI et al, 2015). Adicionalmente, inibidores de transportadores de efluxo podem ser empregados como adjuvantes na terapia antitumoral, proporcionando maior eficácia do tratamento (PEÑA-SOLÓRZANO et al, 2018;SAEED et al, 2018).…”
Section: Dinâmica Molecularunclassified